The need for exercise in exergaming perspective of the uses and gratifications theory - Pham, Thi Tuan Linh; Huang, Han-Chung; Cheng, T.C.E; Wong, May-Kuen; Liao, Yen-Ni; Yang, Ya-Hui; Teng, Ching-I (Industrial management + data systems, 2020)
PurposePlaying exergames may resemble doing conventional exercise and thus has the potential to enhance users’ health. However, no study has yet examined whether and how a need for exercise impacts users’ intention to continuously play exergames, i.e. continuance intention and its antecedents. We developed a model grounded in the uses and gratifications theory (UGT) to address this issue.Design/methodology/approachWe recruited 583 participants to play exergames and collected their psychological responses and physical information. Structural equation modeling (SEM) was used to test the hypotheses.FindingsWe found that health consciousness and perceived exercise benefits are positively related to a need for exercise, which is, in turn, positively related to continuance intention. Moreover, perceived exergame similarity with exercise strengthens the positive link between the need for exercise and continuance intention.Originality/valueThis is the first study using the UGT to explain the underlying mechanism linking health consciousness to continuance intention in the playing of exergames. In addition, we introduced the need for exercise as a novel construct in this study. Our findings provide insights to managers on incorporating health-related features into their exergame products to motivate users' engagement in playing exergames.